The Evolution of Media Discourse Language Across Social Media Platforms - Gharouba SELMA (Akofena)
Abstract: While the media has undergone significant development in the current era, it is expected to continue evolving in the long term. Digital media, along with the new forms of media practices it has introduced (such as social media platforms, blogs, online journalism, chat spaces, and others) necessitates the development of an effective and influential media language. This language should adhere to the desired level of discourse, characterized by specific features in vocabulary, morphology, syntax, and certain distinctions that set it apart from traditional media language. The language of digital media is often simpler, more fluid, practical, direct, contemporary, familiar, and less complex, making it more accessible to various segments of society. This article aims to discuss the importance of media discourse on social media platforms, examining its key characteristics in comparison to traditional media. The discussion will focus on understanding its nature, methods, mechanisms of delivery, and persuasive techniques, while also evaluating the impact of this discourse on the success or failure of communication within society.